Konsep Pendidikan Islam Perspektif Al-Qabisi - Mawaddah; Agus Rahman Waruwu; zizah Hanum OK (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine Al-Qabisi's significant contribution to Islamic education through an in-depth analysis of his famous work,